(Diacyloxyiodo)benzenes‐Driven Palladium‐Catalyzed Cyclizations of Unsaturated N‐Sulfonylamides: Opportunities of Path Selection. Issue 4 (18th January 2017) - Borelli, Tea; Brenna, Stefano; Broggini, Gianluigi; Oble, Julie; Poli, Giovanni
Abstract: A study of the palladium(II)‐catalyzed cyclization of unsaturated N ‐sulfonylamides was undertaken, using (diacyloxyiodo)benzenes as terminal oxidizing agents. Different reactivities were observed as a function of the nature of the unsaturation (terminal vs . internal), or of the hypervalent iodine compound used (diacetoxyiodobenzene vs . bistrifluoroacetoxyiodobenzene). Proper parameter selection allows the direction of the cyclization to be chosen towards either a global aminoacetoxylation, an allylic amination via aminopalladation, or an allylic amination via allylic C–H activation. Abstract :